Light Syntax Parsing and Fuzzy Systems for Rhetorical Structure Theory Text Segmentation - Ali, Omar; Gegov, Alexander; Haig, Ella; Khusainov, Rinat (2021 International Conference on INnovations in Intelligent SysTems and Applications (INISTA), 2021)
We present fuzzy boundaries, a method of segmenting text whereby we consider a population of boundaries to be in a fuzzy-state. Furthermore, we aim to use this method to present a multifaceted segmentation approach that is applicable across various domains that require the use of text segmentation: Text summerisation, Rhetorical Stricture Theory, sentence-based segmentation, paragraph-based segmentation and search-algorithms that require topic-based querying. The work first outlines the subject domain together with previous work surrounding the topic of text segmentation. We move to discussing the rationale, exploring our motivations for such a method. The model and its composition is then described next along side the direction taken in the implementation of the model. We move to the results and performance of our method concluding finally with a discussion on the benefits and justifications for our propositions.